Implementasi Metode Electre Dalam Penentuan Platform yang Tepat dalam Rangka Mewujudkan Flipped Learning di SMK Bali Dewata - Seftian Rusditya; Dewa Gede Hendra Divayana; Gede Indrawan (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
The use of technological resources, especially the internet, has a very important role in supporting the effectiveness of the implementation of the flipped classroom model. Through internet access, students can prepare before face-to-face learning by watching learning videos, reading materials, or doing exercises independently. This allows the classroom teaching and learning process to be more interactive, where face-to-face time can be focused on discussion, problem-solving, and application of concepts. Based on survey data collected from students of SMK Dewata Bali Denpasar, it is known that optimal use of the internet helps increase students' understanding and interest in learning science subjects. However, as time went by, it was found that some of the material was still difficult for students to understand and remember. Therefore, educators need to choose the learning platform that is most effective in supporting the implementation of this model. Using the ELECTRE (Elimination and Choice Expressing Reality) method, this study assessed various platforms such as features, price, ease of use, and user survey results. The results show that Google Classroom is the most suitable and efficient platform to support reverse learning because of its ability to integrate various learning media, ease of access, and support for interaction between teachers and students.